2019
DOI: 10.1039/c9bm00887j
|View full text |Cite
|
Sign up to set email alerts
|

3D printing with peptide–polymer conjugates for single-step fabrication of spatially functionalized scaffolds

Abstract: Solvent-cast 3D printing with peptide–polymer conjugates introduces a versatile platform to spatially organize peptides to guide local cell behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 79 publications
0
35
0
Order By: Relevance
“…[ 55 ] The polymers could further be functionalized with molecules such as nitric oxide to improve hemocompatibility and peptides to support cell adhesion. [ 56 ] Extrusion of cell‐laden hydrogels could also be used to directly print cellular vessel structures composed of materials such as alginate gelatin, and fibrin. [ 57 ]…”
Section: Tissue Engineered Vascular Graftsmentioning
confidence: 99%
“…[ 55 ] The polymers could further be functionalized with molecules such as nitric oxide to improve hemocompatibility and peptides to support cell adhesion. [ 56 ] Extrusion of cell‐laden hydrogels could also be used to directly print cellular vessel structures composed of materials such as alginate gelatin, and fibrin. [ 57 ]…”
Section: Tissue Engineered Vascular Graftsmentioning
confidence: 99%
“…Protocol conjugates [14]. Chemistries become displayed on the surface during fabrication without the need for post-functionalization steps.…”
Section: Pol Scientificmentioning
confidence: 99%
“…This technique thus enables fabrication of diverse and complex architectures as well as spatial presentation of different biochemical cues via layer-by-layer deposition, expanding our ability to fine-tune cell-material interactions. For example, we found that spatially presenting different peptide sequences within the same scaffold significantly affected local cell response [14]. Here, we describe a detailed and stepwise procedure to fabricate and characterize spatially organized constructs for OC tissue engineering as well as how to evaluate zonal tissue formation in response to peptide organization.…”
Section: Pol Scientificmentioning
confidence: 99%
“…Unlike modifications after fabrication, in 2019, Chow et al [ 134 ] introduced a 3D printing method that used the biodegradable polymers poly(caprolactone) (PCL) pre-functionalized with RGDs or RGEs (control) to modify the surface. Fibroblasts preferred to attach and spread on RGDS (biotin)-PCL fibers rather than RGES (azide)-PCL fibers, and increasing the concentration of RGDS (biotin)-PCL can promote cell adhesion.…”
Section: Surfaces and Materials Functionalized With Peptidic Integmentioning
confidence: 99%